Understanding Families Over Time - Edwards, Rosalind. author. aut Link
XVII, 205 p.
Keywords: Drawing on research from the Timescapes Study, this volume discusses the life chances and experiences of children and young people, parents and older generations. A unique qualitative longitudinal study forms the basis for the chapter contributions, delivering policy-relevant findings to address individual and family lives over time.